2016
DOI: 10.1021/acsbiomaterials.6b00103
|View full text |Cite
|
Sign up to set email alerts
|

Processing and Properties of Bioactive Surface-Porous PEKK

Abstract: Bioactive surface-porous polyetherketoneketone materials (PEKK-BSP) were prepared by first leaching hydroxyapatite (HA) microsphere templates from compression molded PEKK/HA composites (i.e., PEKK-P) followed by sulfonation with 80% sulfuric acid for 3 h (i.e., PEKK-SP) and then soaking in a simulated body fluid (SBF) for 5 days. The combination of both physical and chemical processes created a surface-porous PEKK material (PEKK-SP) that had both structurally interconnected and open macropores (200–600 μm) bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 57 publications
1
33
0
Order By: Relevance
“…The bioactivity of Ca‐P ceramics was also evaluated through the bone‐like apatite formation tests. Briefly, simulated body fluid (SBF) was prepared according to previously described (Yuan et al, ). After immersed in SBF for 3 days at 37°C, the samples were taken out and washed gently in deionized water, and then dried at room temperature for bone‐like apatite observation by SEM.…”
Section: Methodsmentioning
confidence: 99%
“…The bioactivity of Ca‐P ceramics was also evaluated through the bone‐like apatite formation tests. Briefly, simulated body fluid (SBF) was prepared according to previously described (Yuan et al, ). After immersed in SBF for 3 days at 37°C, the samples were taken out and washed gently in deionized water, and then dried at room temperature for bone‐like apatite observation by SEM.…”
Section: Methodsmentioning
confidence: 99%
“…Most other examples of porous high performance polymer foams were produced by chemical or physical (gas) blowing [ 13,14 ] or particulate leaching. [ 15,16 ] However, the bulk production of PEEK and PEKK foams, and to a lesser degree PEI foams [ 17,18 ] is still a huge challenge. Gas blowing and particulate leaching methods have limitations restricting their suitability for high performance polymers, because of the small processing window for semicrystalline polymers [ 19 ] and high temperature and pressure requirements.…”
Section: Figurementioning
confidence: 99%
“…So far porous PEKK has only been produced by particulate leaching. [ 15,33,34 ] Reported porosities for porous PEKK obtained by porogen leaching were around 75≈90%, [ 33,34 ] which are close to that achieved by us (77 ± 2%). Converse et al [ 33 ] reported compression properties of porous PEKK produced by porogen leaching, the E‐moduli reported are of the same order of magnitude as those measured by us while the compression strength is identical within error (for a comparison see Figure S4, Supporting Information).…”
Section: Figurementioning
confidence: 99%
“…Compared with PEEK, PEKK has some advantages such as better mechanical performances, higher thermal stability and structural variation between semi-crystalline and amorphous phase as well as versatile chemistry because of two ketone bonds [ 23 ]. Furthermore, PEKK implantable materials have received acceptance by medical implant manufacturers who had gained permit from the U.S. Food and Drug Administration [ 24 ].…”
Section: Introductionmentioning
confidence: 99%